(untitled) (Philological Studies, 2019)
This paper deals with the representation of the concept TERRORISM in the English discourse of news online resources. The research is carried out on the basis of the texts in which the studied concept is verbalized. The choice of the material is influenced by the fact that today’s Internet resources reflect the major trends in the global community, faced with the problem of terrorism.